The role of the hippocampus in navigation is memory - Eichenbaum, Howard (Journal of neurophysiology, 2017)
There is considerable research on the neurobiological mechanisms within the hippocampal system that support spatial navigation. In this article I review the literature on navigational strategies in humans and animals, observations on hippocampal function in navigation, and studies of hippocampal neural activity in animals and humans performing different navigational tasks and tests of memory. Whereas the hippocampus is essential to spatial navigation via a cognitive map, its role derives from the relational organization and flexibility of cognitive maps and not from a selective role in the spatial domain. Correspondingly, hippocampal networks map multiple navigational strategies, as well as other spatial and nonspatial memories and knowledge domains that share an emphasis on relational organization. These observations suggest that the hippocampal system is not dedicated to spatial cognition and navigation, but organizes experiences in memory, for which spatial mapping and navigation are both a metaphor for and a prominent application of relational memory organization.